Chloroplast thioredoxin systems dynamically regulate photosynthesis in plants - Lauri Nikkanen; Eevi Rintamäki (PORTLAND PRESS LTD, 2022)
Photosynthesis is a highly regulated process in photoautotrophic cells. The main goal of the regulation is to keep the basic photosynthetic reactions, i.e. capturing light energy, conversion into chemical energy and production of carbohydrates, in balance. The rationale behind the evolution of strong regulation mechanisms is to keep photosynthesis functional under all conditions encountered by sessile plants during their lifetimes. The regulatory mechanisms may, however, also impair photosynthetic efficiency by overriding the photosynthetic reactions in controlled environments like crop fields or bioreactors, where light energy could be used for production of sugars instead of dissipation as heat and down-regulation of carbon fixation. The plant chloroplast has a high number of regulatory proteins called thioredoxins (TRX), which control the function of chloroplasts from biogenesis and assembly of chloroplast machinery to light and carbon fixation reactions as well as photoprotective mechanisms. Here, we review the current knowledge of regulation of photosynthesis by chloroplast TRXs and assess the prospect of improving plant photosynthetic efficiency by modification of chloroplast thioredoxin systems.